2006
DOI: 10.1111/j.1600-0501.2006.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of different barrier membranes in cultures of human CRL 11372 osteoblast‐like cells: an immunohistochemical study

Abstract: The results demonstrate that cells were able to proliferate on these materials and EG promoted the proliferation of human osteoblast like cells. We prefer to use the EG membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…In the present study the results showed that collagen membrane presented lower values than PLA membrane which are similar to Chandrahasa, et al 2011 [19], Parrish et al 2009 [4] and [14]. Polylactic acid and collagen membranes’ biocompatibility was evaluated in vitro using osteoblast-like cells.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study the results showed that collagen membrane presented lower values than PLA membrane which are similar to Chandrahasa, et al 2011 [19], Parrish et al 2009 [4] and [14]. Polylactic acid and collagen membranes’ biocompatibility was evaluated in vitro using osteoblast-like cells.…”
Section: Discussionsupporting
confidence: 88%
“…Polylactic acid and collagen membranes’ biocompatibility was evaluated in vitro using osteoblast-like cells. The results showed proliferation capacity in both types of materials, but better results were found polylactic acid membrane PLA group [14]. In a systematic review, it was observed that the use of polylactic acid membrane even shows better results than open flap debridement with grafts [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More intensive cell reaction on the “foreign body” (PLGA, PLGA+CF) took place after 48 hours – resulting in the highest cytotoxicity values. Additionally, the cumulative toxic influence of all the materials upon the osteoblasts used in the first two periods (24 h, 48 h) could be caused by the inevitable chemical reactions characteristic of the test employed [12,29]. …”
Section: Resultsmentioning
confidence: 99%
“…The kind and the origin of the cells used are of particular importance, as well as the way they are put in contact with the samples of the examined material [12,13,21,25]. With regards the performance of the cells, their activity is influenced by the kind of the polymer base, which can vary depending on the processing method, the kind of modifying phase, the size of the filler particles, surface topography, porosity, resorption degree or the molecular weight [30].…”
Section: Resultsmentioning
confidence: 99%